SANSKRIT STUDIES IN THE RIVER ISLAND MAJULI: AN OVERVIEW - Borah, Profulla (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The Sanskrit Language is the basis of Great Indian civilization and culture. The Sanskrit language and its diverse cultures have established India in a remarkable position in the realm of world civilization. Among all the languages in India, Sanskrit has occupied a prominent place from the distinct past to present. The field of Sanskrit language across India is persistent and Indianness is never complete except for it.